UiTM Mukah hosts final leg of the 2025 knowledge aspiration tour - Kamaruddin, Siti Faridah; Joseph, Stefanie Natasha Rich; Robert, Cindy; Juhari, Nur Nadia Qausar; Bohari, Mohamad Musa (Corporate Communication Unit, UiTM Mukah Campus, 2025)
The initiative targeted Form Four students, focusing on enhancing public speaking skills and promoting the effective use of scientific calculators. Each school visit presented a unique learning experience, shaped by the diverse responses of the students. At SMK Mukah, the “Say It Right” seminar was delivered by Ms Siti Faridah Kamaruddin, an alumna of the school. Participants responded positively, actively engaging in Q&A sessions and working closely with APB lecturers who facilitated the programme. These lecturers shared their expertise in language and guided students in preparing effective public speaking scripts.